Thoughts and Concerns of Spanish Teachers on Returning to School After the COVID-19 Pandemic - Alberto Sanmiguel-Rodríguez; Raquel Leirós-Rodríguez; Víctor Arufe-Giráldez; Andrea García-Fernández; José Luís García-Soidán; Rubén Navarro-Patón (Revista Electrónica Educare)
Introduction. At the beginning of the 2020-2021 academic year, the government, health organizations, and educational institutions had to face the implementation of protocols and action plans within the classrooms to prevent COVID-19. Aim. This study aimed to analyze the thoughts and concerns of Spanish teachers during the academic year 2020-2021. Method. The study involved the participation of 965 teachers (74.3% Women; Mage = 43.5 9.9). An ad hoc questionnaire comprising 38 items was utilized, focusing on the resources offered by the administration for the return to classrooms, teachers’ concerns about this new academic year, and their thoughts on ideal teaching conditions. Results. Differences were observed based on age and gender in the management (P1) (p = 0.02) and support (P2) (p = 0.04) from the educational administration, perceived security (P3) (p = 0.01), reduction of the working day (P5) (p = 0.002), and the adequacy of material (P6) (p = 0.004) and human (P8) (p = 0.04) resources. Teachers with greater experience exhibited differences in the items P2 (p = 0.03), P3 (p = 0.03), and P8 (p = 0.03). Conclusions. Less experienced teachers expressed higher levels of concern, while those with more teaching experience highlighted the need for additional human resources and training.